Allergic drug reaction to diclofenac [Voveran] in the management of pelvic inflammatory disease with moderate anemia - Sultana, Fatima; Sajida, Shabnam; kandukuri, durga mounika (Indian Journal of Case Reports, 2026)
The allergic drug reaction of diclofenac, examined in this case study, investigates and highlights the need for promptly identifying the signs and symptoms of an adverse drug reaction in the treatment of pelvic inflammatory disease (PID). Diclofenac (VOVERAN 1 mL twice daily) was administered intramuscularly to a 31-year-old female patient to treat PID. The patient was identified as having a documented history of allergic medication responses and was then evaluated for lowering allergic responses by a primary care physician’s opinion. The patient was currently complaining of rashes all over the body, itching, and nausea. Together with clinical features and provisions of complete blood picture, complete urine examination, and urine culture sensitivity test revealed PID with moderate anemia. Diclofenac is a non-steroidal anti-inflammatory drug that helps to manage the pain and inflammation caused by PID.